History of epidemiological myopia research in Poland after World War II - D. A. Czepita; A. Kładna (Российский офтальмологический журнал)
So far, no article concerning the history of epidemiological studies on myopia in Poland after World War II has been published. Therefore, the aim of the work is to present the history of epidemiological studies on myopia in Poland after World War II. In order to obtain answers to the research questions, studies of source and archival materials were conducted. It turned out that the leading centers in Poland conducting research on myopia were the Pomeranian Medical University in Szczecin and the Medical University of Silesia in Katowice.